SURGICAL EXCISION COMBINED WITH SUPERFICIAL RADIATION THERAPY FOR THE TREATMENT OF PUBIC KELOIDS: A TWO-CASE SERIES (Tạp chí Y học Cộng đồng, 2026)
Keloids of the pubic region are rare lesions that are difficult to treat and highly prone to recurrence. We report two female patients with pubic keloids of 35–45 years’ duration, initially developing after acne-like inflammatory lesions and refractory to conservative treatment. One patient had previously undergone surgical excision with full-thickness skin grafting but developed severe recurrence. Diagnosis was established based on clinical and histopathological findings. Both patients underwent complete surgical excision combined with multilayer tension-reducing closure and early postoperative superficial radiotherapy with a total dose of 18 Gy. Primary wound healing was achieved in both cases without significant complications. Long-term follow-up at 2–3 years demonstrated marked improvement in pain, pruritus, and scar characteristics, with high patient satisfaction. Combined surgical excision and superficial radiation therapy may represent an effective therapeutic option for recurrent pubic keloids.
Keywords: keloid; pubic region; superficial radiation therapy.